Pengaruh harga dan kualitas terhadap keputusan pembelian tembakau PT.Djarum di kalangan pengepul di Madura - Fadilatus Syammil; Burhanudin Burhanudin (Journal of Business & Banking, 2018)
Indonesia is a grand producer of tobacco, and including the province of East Java, Pamekasan Regency, Madura. Pamekasan Regency produces the most tobacco compared to Sumenep Regency and Sampang Regency. Tobacco attracts the interest of the Indonesian cigarette companies. PT. Djarum purchases tobacco to be used as a material to produce cigarettes. The purchase of tobacco is based on the prices and the quality. This company purchases a huge amount of tobacco, which is nine thousand tons. The aim of this research is to analyze the signification effect of the price and the quality towards PT Djarum’s purchasing decision of tobacco among collectors in Madura. The respondents of this research are the collectors (Pengepul/Bandul) of PT Djarum. The questionnaires are given to seventy respondents and is analyzed using Partial Least Square (PLS)-Structure Equation Model (SEM). The results of this research show that the price has a significant positive effect towards the tobacco purchasing decision of PT. Djarum. The quality not significant negative effect towards the tobacco purchasing decisions of PT. Djarum.